A Global Update on COVID-19 Pandemic: A Global Update on COVID-19 Pandemic - Hassan, Taimoor (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
As of October 10, 2021, the entire planet has reported 219 million COVID-19 cases, with 4.55 million fatalities. Lockdowns and softening measures have been thrown into turmoil throughout the world since the outbreak. Our social life will only return to normal once an appropriate vaccine is produced and proper authorized preventive techniques are implemented. To tackle this pandemic, governments and health experts all around the globe are experimenting with a range of measures and preventative strategies. So far, 22 vaccines have been approved. They are effective against immunocompromised people, pregnant women, and multiple sclerosis patients. Certain nations are considered to be more successful than others in terms of providing safety to their inhabitants and increasing their economic activities. A plethora of vaccinations have been produced, and a research anthology has been published. However, medical personnel are still searching for a viable treatment to limit this pandemic.